Head and Neck Paragangliomas: 16-year Single-center Experience and Mini Review on Diagnosis, Treatment, and Follow-up - Gokce AYDEMIR; Fazil Necdet ARDIC; Cuneyt Orhan KARA; Ferda BIR (Medeniyet Medical Journal)
Objective: To investigate head and neck paraganglioma cases treated at a tertiary center from 2007 to 2023. The research includes a thorough examination of published studies that have focused on long-term outcomes. The additional goal is to contribute to the existing knowledge on head and neck paraganglioma, with a particular emphasis on refining diagnostic algorithms, treatment selection, and follow-up procedures. Methods: A total of 44 patients were retrospectively analyzed, and 39 were included. Demographic information, symptoms, radiological examination results, types, stages, and postoperative complications were recorded. A review was conducted to select articles that reported single-center experiences with large cohorts, long follow-ups, and different treatment modalities since 2010. Results: The mean age of the patients was 54 years, and the female/male ratio was 3.55: 1. Among the 39 cases examined, 18 and 19 were identified as cervical paraganglioma and 19 as temporal bone paraganglioma. All patients initially underwent surgical resection. The mean follow-up duration was 5.42 years. Four residual cases and two recurrences were identified postoperatively, and a Gamma Knife was used as additional treatment. Subsequently, 17 articles were selected and summarized, and then a flowchart was prepared showing the possible options for diagnosis, treatment, and follow-up. Conclusions: Preoperative staging is essential for surgical planning and predicting potential intraoperative complications. Based on our findings and review of the articles, we have prepared a flowchart that includes all possibilities depending on the tumor stage to help in the diagnosis, treatment, and follow-up of head and neck paragangliomas.